Kawasaki disease in Greek children: a retrospective study. (24th February 2012) - Alexopoulos, A.; Vekiou, A.; Lycopoulou, L.; Tavena, A.; Lagona, E.; Kakourou, T.
Abstract Background The studies of series of children with Kawasaki disease (KD) in Greek children are limited. Objectives To evaluate the epidemiology, clinical manifestations, laboratory findings, course and outcome of complete KD in Greek children. Methods Patients with complete KD who were discharged from our hospital and followed up routinely between 2004 and 2011 were included in the study. The relevant data were collected using a standardized form. Results There were 49 children (27 boys, 22 girls), mean age: 2.14 years. A seasonal peak of the disease during spring and summer months was detected. Changes of the extremities and cervical adenopathy were the least commonly met criteria for the complete KD diagnosis. The mean time of starting treatment was 6.5 days from the disease onset. The majority of patients, 42/49, responded well to a single infusion of intravenous immunoglobulin (IVIG), while 7/49 patients who had persistent fever despite initial therapy with IVIG needed additional treatment with either a second dose of IVIG(5), intravenous pulse of methyl prednisolone(1) or infliximab(1). Coronary artery abnormalities were detected echocardiographically in 17/49 patients. Most of them (15/17) developed transient dilatations which resolved by the 8th week of disease onset while only 2 patients, despite early onset of treatment, developed coronary artery aneurysms which required coronary artery bypass grafts at a later stage. Conclusions Major epidemiologic features of KD detected among Greek children are similar to those reported in other populations. This study also demonstrates that significant cardiac complications may still occur following the disease even if it is diagnosed and treated early.